2015
DOI: 10.3906/tar-1405-134
|View full text |Cite
|
Sign up to set email alerts
|

Effects on growth of persimmon (Diospyros virginiana) rootstock of arbuscular mycorrhizal fungi species

Abstract: Persimmon (Diospyros kaki Thunb.) is grown in many parts of the world that display subtropical climate conditions, including Turkey. There are 2 common rootstocks used in its production: D. kaki and D. virginiana Thunb. Arbuscular mycorrhiza (AM), a symbiosis between plant roots and members of an ancient phylum of fungi, Glomeromycota, improves root development, water supply, and nutrients such as phosphate and zinc in the host plant. In this study, the effects of 5 AM fungi species (Glomus mosseae, G. clarium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…The response to AMF inoculation differs according to the plant species studied. The species of Diospyros virginiana inoculated with C. etunicatum showed higher height and dry matter production of shoots and roots (INCESU et al, 2015). Similar results were found in the study of AMF inoculation in Passiflora alata seedlings, observing a positive influence on the growth variables, with higher values in shoot dry matter production and height of plants colonized by G. margarita and G. clarum (RITER NETTO et al, 2014).…”
Section: Resultssupporting
confidence: 66%
“…The response to AMF inoculation differs according to the plant species studied. The species of Diospyros virginiana inoculated with C. etunicatum showed higher height and dry matter production of shoots and roots (INCESU et al, 2015). Similar results were found in the study of AMF inoculation in Passiflora alata seedlings, observing a positive influence on the growth variables, with higher values in shoot dry matter production and height of plants colonized by G. margarita and G. clarum (RITER NETTO et al, 2014).…”
Section: Resultssupporting
confidence: 66%
“…Ndoye et al (2016) found that the frequencies and highest intensities of mycorhization of the roots of fonio (Digitaria exilis) seedlings with G. aggregatum and R. irregularis. In addition, Incesu et al (2015) observed rates of higher root colonizations of Diospyros virginiana with R. irregularis and G. caledonium compared with other species of arbuscular mycorrhizal fungi (G. etunicatum, F. mosseae and G. clarium). Smith et al (2009) explained this by the capacity of a plant to develop a symbiotic association of preferential type with a species of arbuscular mycorrhizal fungi although it is colonized by various species of arbuscular mycorrhizal fungi, involving different rates of colonization on roots while McGonigle and Fitter (1990) explain these differences in effect by an ecological specificity.…”
Section: Discussionmentioning
confidence: 85%
“…Also, the species D. heterogama and A. morrowiae had the most beneficial effects on seedling growth and may have the most positive effects on agricultural production, as they show potential for use in seedling production on a commercial scale. The AMF species included in this study, which preferentially colonized persimmon seedlings, differ from the species studied by Matsubara and Hosokawa (1999), Marin et al (2003) and Incesu et al (2015). Several studies have reported that soil characteristics such as moisture, structure, and fertility (Lekberg et al, 2007;Egerton-Warburton et al, 2007), as well as plant species (Alguacil et al, 2011;Torrecillas et al, 2012) influence the composition of AMF communities and their colonization potential.…”
Section: Discussionmentioning
confidence: 89%
“…Although in our findings the inoculation with the genera Rhizophagus and Claroideoglomus did not significantly promote increases in seedling growth, in previous studies the two genera had increased the growth of persimmon seedlings. Incesu et al (2015) Although there are no reports of D. heterogama and A. morrowiae affecting the height of persimmon seedlings, their effects on other agronomic fruit species have been reported. For example, Silveira et al (2002) evaluated the use of six AMF species for the inoculation of rootstocks for the production of avocado (Persea sp.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation